An Investigation Of Reading Strategies Employed By Thai Efl Lower Secondary Students In Science Ability Programme - Kritchada, Ruangnoi (2022)
This study investigated the effectiveness of reading strategies employed by Thai EFL lower secondary students of Science and Math’s Ability program at one private, and two government secondary schools in Southern province of Thailand. The integration fo cognitive, metacogtive, determination, social, and memory strategies that form the reading training program were expected to enhance the students’ reading strategies instruction techniques. The sample of the study were thirty, grade seven students selected based on National English Test of Thailand. Quantitative and qualitative data were obtained from three primary sources; Pre- and Post-test from scientific modules, and interviews. The quantitative research instrumentation consisted of an adapted version of Metacognitive Awareness of Reading Strategies Inventory-Revised (MARSI-R) by Mokhtari and Reichard, (2013) and reading comprehension exam as pre and post-test.